First Presentation of Systemic Lupus Erythematosus in a 24-Year-Old Male following mRNA COVID-19 Vaccine - Yael Raviv; Batya Betesh-Abay; Yuliya Valdman-Grinshpoun; Liora Boehm-Cohen; Michael Kassirer; Iftach Sagy (Case Reports in Rheumatology)
The SARS-CoV-2 viral pandemic has had an immeasurable global impact, resulting in over 5 million deaths worldwide. Numerous vaccines were developed in an attempt to quell viral dissemination and reduce symptom severity among those infected. Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by the production of antinuclear autoantibodies (ANAs) with heterogenic clinical manifestations, secondary to immune complex deposition in a multitude of organ systems. There are scarcely reported cases of SLE development following COVID-19 mRNA vaccination. We present a case of a 24-year-old male without preexisting conditions or family history of autoimmune disorders, presenting with SLE following the first dose of the SARS-CoV-2 Pfizer-BioNTech mRNA vaccine.